Author Response: Kidney Function, Kidney Function Decline, and the Risk of Dementia in Older Adults. (16th November 2021) - Xu, Hong; Garcia-Ptacek, Sara; Lindholm, Bengt; Eriksdotter, Maria; Carrero, Juan Jesus
Abstract : We thank Dr. Fischereder for the comments on our study. 1 Our goal was to explore the association between kidney function and the risk of dementia, not to imply causation. Although the underlying mechanisms remain unclear, they do not preclude our findings from being plausible. Subsequent studies confirm an association between cognitive impairment and markers of kidney dysfunction. 2, 3 Experimental evidence suggests that uremia-induced chronic inflammation, oxidative stress, hypercoagulation, vitamin-D deficiency, klotho deficiency, hyperparathyroidism, anemia, and impaired peripheral amyloid-β clearance may lead to dementia. 4 Besides, chronic kidney disease (CKD) may be a risk mediator for other conditions that cause dementia, such as smoking, hypertension, diabetes, and lipid disorders. 4 It is important to note that our study reported similar associations in persons with and without diabetes or hypertension.